The roles of task-specific forecasting experience and innate ability in understanding analyst forecasting performance - Clement, Michael B.; Koonce, Lisa; Lopez, Thomas J. (Journal of Accounting and Economics, 2007)
Considerable debate exists about what analyst experience measures and whether analysts learn from their experiences. Extant research has argued that once innate ability is considered, analysts’ general and firm-specific experiences are not relevant to understanding their forecasting performance. We argue that measures of experience need to be expanded to also include task-specific experience. Our results reveal that analysts’ forecast accuracy is associated with both their innate ability and task-specific experience. In addition, we find that forecast accuracy and task-specific experience are most highly correlated for those analysts who survive the longest and, thus, presumably have the greatest innate abilities.